Geographic distribution of staphylococcus spp. infections and antimicrobial resistance among dogs from Gauteng Province presented at a veterinary teaching hospital in South Africa. (February 2019) - Qekwana, Daniel Nenene; Oguttu, James Wabwire; Odoi, Agricola
Abstract: The objective of this study was to investigate spatial patterns of staphylococcal infections and resistance patterns of clinical isolates among dogs from Gauteng province in South Africa. Data from records of 1497 dog clinical samples submitted to a veterinary teaching hospital between 2007 and 2012 were used in the study. Spatial empirical Bayesian smoothed risk maps were used to investigate spatial patterns of staphylococcal infections, antimicrobial resistance (AMR), and multidrug resistance (MDR). Moran's I and spatial scan statistics were used to investigate spatial clusters at municipal and town spatial scales. Significant clusters of staphylococcal infections were identified at both the municipal (Relative Risk [RR] = 1.71, p = 0.003) and town (RR = 1.65, p = 0.039) scales. However, significant clusters of AMR ( p = 0.003) and MDR ( p = 0.007) were observed only at the town scale. Future larger studies will need to investigate local determinants of geographical distribution of the clusters so as to guide targeted control efforts.